Not being Miriam - Campbell, Marion (Fremantle, Western Australia : Fremantle Arts Centre Press, 1988)
Deals with childhood, adolescence, motherhood and old age, with work, love, and abandonment, but especially with the power of identification.
Keywords: Short stories, Australian